Functional correlations between specific leaf area and specific root length along a regional environmental gradient in Inner Mongolia grasslands. (5th October 2015) - Cheng, Junhui; Chu, Pengfei; Chen, Dima; Bai, Yongfei
Summary: Among above‐ and below‐ground traits, specific leaf area (SLA, cm 2  g −1 ) and specific root length (SRL, m g −1 ) are the two key traits reflecting species resource acquisition strategies. However, patterns of variation in SLA and SRL have rarely been examined simultaneously across evolutionary history and environmental gradients, and the SLA–SRL relationship is still controversial on several grounds. We examined the inter‐ and intraspecific variations in SLA and SRL of different root branching orders and the SLA–SRL relationship across 55 species and 21 plant communities of four vegetation types along a 2000‐km transect in the Inner Mongolia grassland. With increasing root branching order, the interspecific variation in SRL increased, but the intraspecific variation in SRL decreased considerably, and the form of SLA–SRL relationship shifted from positive to negative. This indicates that acquisition of soil resources (e.g. water and nutrients) is a fundamental strategy for plant investment to root length. When inter‐ and intraspecific variations in SLA and SRLs were partitioned into alpha (within‐community) and beta (among‐community) components, the alpha component exhibited substantially greater inter‐ and intraspecific variations than the beta component. Across the transect, the evolutionarily late diverged species in phylogenetic tree evolved towards low SLA and SRL‐1 (SRL for first‐order roots) and tended to distribute in resource‐poor conditions along the environmental gradient. The early diverged species, in contrast, had high SLA and SRL‐1 and mostly distributed in resource‐rich conditions. Our findings suggest that patterns of inter‐ and intraspecific variations in SLA and SRL of different root branching orders and the form of SLA–SRL relationship could be well explained by within‐ and among‐community filtering processes and species divergence time. Coordination and trade‐offs between leaves and roots do not mutually exclude but operate simultaneously at different scales and among different root branching orders in arid and semi‐arid grasslands. Abstract : Lay Summary